Bulgaria’s EU accession negotiations: achievements and challenges - Velichkov, Kamen (Papeles del Este, 2004)
As elsewhere in Central and Eastern Europe, in Bulgaria, membership in the European Union tops the political agenda. Ever since their inception, the EU accession negotiations acquired central place in the internal discourse on Bulgaria’s transition. For all practical purposes they became the concise and comprehensive equivalent of the progress in economic and administrative reforms. In taking stock of the state of affairs in Bulgaria’s negotiations with the EU as of the year 2003, the author attempts to provide the interested public with a factual background in terms of harmonization, institutional capacity building and implementation policies. Not surprisingly the text indicates that in certain areas the negotiations triggered the reform effort itself and defined its timetable. The kaleidoscopic overview leads to reasonably optimistic forecasts about the chances of Bulgaria to accede to the European Union in the not so distant future.